Behaviour based safety implementation and comparison in a chemical manufacturing industry [electronic resource] - Siti Nurlaily Muhamad Yussof, 1988- (2014)
Thesis (Sarjana Kejuruteraan (Kejuruteraan Industri)) - Universiti Teknologi Malaysia, 2014